Elevated Transforming Growth Factor-β2 in the Aqueous Humor: A Possible Explanation for High Rate of Capsular Contraction Syndrome in High Myopia - Keke Zhang; Xiangjia Zhu; Minjie Chen; Xinghuai Sun; Jin Yang; Peng Zhou; Yi Lu (Journal of Ophthalmology)
Purpose. The purpose of the study was to elucidate the role of transforming growth factor-beta 2 (TGF-β2) in the development of high myopic capsular contraction syndrome. Methods. Nineteen cases of capsular contraction syndrome, including 14 with high myopia, were collected, and their clinical data were reviewed. Aqueous humor and anterior capsular membranes were obtained during capsulotomy. Hematoxylin-eosin and immunohistochemical staining with anti-TGF-β2 antibody were performed on capsular membranes. TGF-β2 levels in aqueous humor were assayed using ELISA and western blot. Results. High myopia was significantly associated with the incidence of capsular contraction syndrome (odds ratio: 14.74, P<0.001, 95% CI: 5.29–41.05). Histopathological analysis revealed proliferation of fibroblast-like lens epithelial cells on the shrunken anterior capsule, labeled with TGF-β2 antibodies. ELISA and Western blot showed higher levels of TGF-β2 in aqueous humor of patients with capsular contraction syndrome and high myopia. Conclusions. High myopia is a risk factor for capsular contraction syndrome. Elevated TGF-β2 levels in high myopic cataract patients may play an important role in the pathogenesis of capsular contraction syndrome.